Digitalization of Village-Owned Enterprises in Supporting SDGs in Rural Areas: Opportunities and Challenges in Sigi Regency - Umar; Cahyaning Raheni; Rizkiani Iskandar (www.amertainstitute.com, 2025)
This article examines the complex relationship between the digitalization of Village-Owned Enterprises (BUM Desa) and their contribution to the Sustainable Development Goals (SDGs) in rural areas, focusing on the specific opportunities and challenges in Sigi Regency, Central Sulawesi. Based on a qualitative case study methodology, the research identifies that digitalization offers significant opportunities for BUM Desa, including expanding market reach, improving operational efficiency and transparency, and increasing access to capital. These opportunities directly support several SDGs, such as poverty eradication (SDG 1), equitable economic growth (SDG 8), and strengthened partnerships (SDG 17). However, the findings also highlight that realizing this potential is significantly hampered by fundamental challenges in Sigi Regency. These challenges include limited human resource capacity and digital literacy, uneven digital infrastructure, insufficient capital and small business scale, suboptimal organizational management, and a lack of coordination among stakeholders. The study concludes that while digitalization is a powerful tool, its effectiveness is highly dependent on a strong foundation of capacity and governance. Without addressing these structural issues, digitalization risks widening existing disparities or failing to deliver the expected transformative impact. This research provides a nuanced understanding of how digitalization, BUM Desa, and SDGs interact in a challenging socioeconomic and geographical context, emphasizing the need for a holistic and tailored digitalization strategy that combines technological investment with human capacity building and institutional strengthening.